Repeated measures of implementation variables - Fixsen, Dean L.; Van Dyke, Melissa K.; Blase, Karen A. (Frontiers in Health Services, 2023)
If implementation independent variables and implementation dependent variables are to contribute to a science of implementation, then there must be commonly used measures of implementation processes and outcomes. The lack of usable and repeatable measures has slowed the development of a science of implementation. In practice, implementation specialists and researchers are doing the work of implementation and studying the results in a wide variety of applied settings. They continually deal with complexity and confounders to accomplish their implementation practice and science aims and have developed measures of implementation variables. A review of the literature was undertaken to “see what is being done” to evaluate implementation variables and processes in situations where achieving outcomes was the goal. No judgement was made about the adequacy of the measure (e.g., psychometric properties) in the review. The search process resulted in 32 articles that met the criteria for a repeated measure of an implementation variable. 23 different implementation variables were the subject of repeated measures. The broad spectrum of implementation variables identified in the review included innovation fidelity, sustainability, organization change, and scaling along with training, implementation teams, and implementation fidelity. It is heartening to see the breadth of implementation-specific variables that have been measured two or more times in one or more studies. Given the long-term complexities involved in providing implementation supports to achieve the full and effective use of innovations, repeated measurements of relevant variables are needed to promote a more complete understanding of implementation processes and outcomes.